Ensuring the performance of external communications: An informal classification of target groups - Mikhail V. Rodchenkov (Управленец)
The increasing influence of the investment community on business sustainability highlights the need for a compre hensive understanding and accurate segmentation of this audience. The research aims to identify consistent criteria for intra group differentiation in the perception of financial reporting information among members of various stakeholder groups in or der to improve the performance of external communications management. Methodologically, the study rests upon stakeholder theory, which is supported by expert assessments, structural-logical analysis, and multidimensional discriminant analysis. The study draws on authentic data of a survey on the quality of corporate reporting information conducted in the fourth quarter of 2020 among 52 representatives of the Russian business. The research identifies motivationally-rooted statistically significant discrepancies in the probability of correlating some survey participants with their functional group formed on a formal basis. We discuss the relevant criteria for an informal division of respondents into groups based on subjective judgments about qualitative characteristics of corporate financial reports. These criteria include variations in estimates of complexity of reporting standards and functionality of cost indicators based on the concept of fair market value. The revealed criteria for motivational and func tional identification within stable subgroups of financial statement users formed within functional groups represents the scien tific novelty of this study. The results contribute to a deeper understanding of the relevant criteria for the group structure of the investment community, which constitutes the target audience for corporate reporting. These findings can be utilized to refine the formal classification of users of reporting information, as well as to adjust other components of corporate management systems with the aim of enhancing the effectiveness of external communications.